Development Of Ppkn Interactive E-Module To Increase High School Students' Understanding Of Threats To The Position Of The Republic Of Indonesia - Estiva Estiva; Suyato Suyato (Research Psychologie, Orientation et Conseil, 2024)
This research aims to develop a PPKn Interactive E-Module to increase students' understanding of SMA Negeri 1 Malinau regarding threats to the position of the Republic of Indonesia. It is hoped that the use of innovative learning media can improve the quality of learning and students' understanding of the material being taught. The development of this E-Module uses the ADDIE method, which consists of five stages: Analysis, Design, Development, Implementation and Evaluation. The final product is tested for suitability by experts. The material expert's assessment resulted in an average score of 3.8 with a percentage of 95%, which is in the "very decent" category. The media expert's assessment resulted in an average score of 3.87 with a percentage of 97%, also in the "very decent" category. The average result of the material and media validator assessment is 3.83 with a percentage of 96%, indicating that this Interactive E-Module is "very suitable" to be used as teaching material regarding threats to the position of the Republic of Indonesia. Product effectiveness testing was carried out through pre-test and posttest, with the t test results showing a significant value (sig) = 0.000, smaller than ? 0.05, so that Ho was rejected and Ha was accepted. The students' average pre-test score was 55.00 and the posttest average score was 85.83, indicating an increase of 30.83. This indicating that there is a significant increase in understanding among class XI students after using the PPKn Interactive E-Module on material regarding threats to the position of the Republic of Indonesia. Thus, the PPKn learning E-Module for class XI at SMA Negeri 1 Malinau is effective in increasing students' understanding of this material